2016
DOI: 10.1212/wnl.0000000000003409
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of the collection of patient-reported outcomes in an ambulatory neurology clinic

Abstract: Objective: To determine whether patients could self-report physical and mental health assessments in the waiting room and whether these assessments would be associated with modified Rankin Scale (mRS) and Quality of Life in Epilepsy (QOLIE-10) scores.Methods: We offered iPad-based surveys to consecutive adult neurology patients at check-in to collect patient-reported outcome measures (PROMs). We collected demographic and clinical data on 6,075 patients through survey or administrative claims and PROMs from par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…Lastly, one out of four patients received help to answer the questions. This may have increased the T-scores since proxy's tend to report worse patient-reported outcomes compared to the patient (20,22).…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, one out of four patients received help to answer the questions. This may have increased the T-scores since proxy's tend to report worse patient-reported outcomes compared to the patient (20,22).…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have shown that increasing age is associated with decreased preference for tablet questionnaires over paper version [ 27 ], increased time needed to complete tablet questionnaires [ 38 ], and increased difficulty using tablets [ 6 , 11 , 22 , 28 , 29 ]. However, others have reported no significant influence of increasing age on tablet questionnaire usability, feasibility, and preference over paper versions [ 4 , 5 , 25 , 39 ]. Interestingly, being older than 65 years of age was not associated with failure to complete the tablet questionnaire in patients who accepted it.…”
Section: Discussionmentioning
confidence: 99%
“…e-PRO is a term used by some to indicate electronic-entered PROs, which provide information comparable to that provided by questionnaires completed on paper [108,109,110], and have the added benefit of not requiring separate data entry. Sometimes the entry is at the time of the visit with the clinician, either via a kiosk [111] or a tablet [112]. When this is completed before seeing the clinician, the information can be available just before or during the visit.…”
Section: Characteristics Of the New Systemmentioning
confidence: 99%